High‐Performance of Gas Hydrates in Confined Nanospace for Reversible CH4/CO2 Storage. Issue 29 (6th June 2016) - Casco, Mirian E.; Jordá, José L.; Rey, Fernando; Fauth, François; Martinez‐Escandell, Manuel; Rodríguez‐Reinoso, Francisco; Ramos‐Fernández, Enrique V.; Silvestre‐Albero, Joaquín
Abstract: The molecular exchange of CH4 for CO2 in gas hydrates grown in confined nanospace has been evaluated for the first time using activated carbons as a host structure. The nano‐confinement effects taking place inside the carbon cavities and the exceptional physicochemical properties of the carbon structure allows us to accelerate the formation and decomposition process of the gas hydrates from the conventional timescale of hours/days in artificial bulk systems to minutes in confined nanospace. The CH4 /CO2 exchange process is fully reversible with high efficiency at practical temperature and pressure conditions. Furthermore, these activated carbons can be envisaged as promising materials for long‐distance natural gas and CO2 transportation because of the combination of a high storage capacity, a high reversibility, and most important, with extremely fast kinetics for gas hydrate formation and release. Abstract : Thermal stability of gas hydrates (CH4 and CO2 ) confined in the cavities of high‐surface area activated carbons have been evaluated for the first time using synchrotron X‐ray powder diffraction. This knowledge has been used to successfully exchange in situ CH4 for CO2 at practical temperature and pressure conditions (see figure).